Semaglutide and the Skin: An Overview of Current Evidence - Gołąbek, Natalia; Szymański, Łukasz; Mordarska, Milena; Merc, Artur; Piątek, Przemysław; Kodura, Alicja; Piwowarczyk, Alicja; Łozowski, Jan; Paluchowska, Joanna; Białas, Julia (Quality in Sport, 2026)
Background. Semaglutide is a GLP-1 receptor agonist with 94% sequence homology to human GLP-1. GLP-1 plays a role in the physiological regulation of appetite and energy intake. Aim. This review summarizes current evidence on the effects of semaglutide on skin conditions and its cutaneous adverse reactions. Materials and methods. A literature search was conducted in PubMed and Google Scholar databases using the keywords: “semaglutide”, “skin”, “glp-1 receptor agonists”, “dermatology”. Meta-analyses, systematic reviews, original studies, clinical trials, case series, and case reports in English were included without time restrictions. Eligible studies involved human subjects and provided data on semaglutide’s effects on skin diseases and/or cutaneous side effects. Reference lists were also screened for additional relevant articles. Results. Available literature indicates potential therapeutic benefits of semaglutide in several skin disorders, including hidradenitis suppurativa and psoriasis. However, reports of cutaneous adverse reactions and newly emerging skin conditions have also been documented. Conclusions. Semaglutide may offer therapeutic value in dermatological conditions such as psoriasis and hidradenitis suppurativa, however cutaneous adverse reactions have also been reported. Further research is required to clarify its clinical utility and safety profile in dermatology.